Non-communicable disease prevention, nutrition and aging - Ruthsatz, Manfred; Candeias, Vanessa (Acta Biomedica Atenei Parmensis, 2020)
Nutrition plays a decisive role across geographies and societal groups in contributing to human health, strengthening resilience and extending the period of being free from non-communicable diseases (NCD) and increasing the quality of life. The objective of this review article is to shed some light on the multiple, often interconnected facets of the increased healthy longevity of populations, one of the greatest success stories humanity has achieved over the last century. Multiple stakeholders need to align to overcome some of the protective ‘hurdles’ established over decades that focus on treating diseases rather than preventing them whenever possible, and to create coherent policies and incentives with respect to individuals and healthcare systems in order to enable healthier populations.